Exception handling in component composition with the support of middleware. - Feng, Yaodong (Software engineering notes.)
Exception handling is a practical and important way to improve the reliability of a software system. In component based software engineering, exceptions are usually handled by the developers of reusable components. However, many exceptions are dependent on the context of a component in the target system. Such exceptions are difficult and sometimes impossible to be handled at the stage of development of reusable components. On the other hand, we found out that many exceptions can be successfully handled by some special mechanisms of middleware. In this paper, an approach to handling the exceptions in the component composition with the support of middleware is proposed. We define an exception handling model complementary to the software architecture for identifying and analyzing the exceptions and taking the knowledge of supporting middleware into the decision of exception handling. The feasibility and effectiveness of the approach are demonstrated through a J2EE blueprint program.